"I don't think anybody really knows": Constructing reflexive ignorance in climate change adaptation. (11th February 2021) - Bowden, Vanessa; Nyberg, Daniel; Wright, Christopher
Abstract: Responding to the existential threat of climate change is often seen as requiring greater reflexivity. Imbued with notions of resilience and reflection, reflexivity is assumed to contribute to pro‐environmental change. However, as the need to manage climate impacts becomes more immediate, political struggles over climate adaptation have become increasingly apparent. These impacts occur most often within local communities, in the context of competing economic interests and differing interpretations of climate science. Thus while it is increasingly difficult to deny climate change, conflicting priorities can lead to ignorance. In these circumstances, how communities build and share knowledge, and negotiate responses is central. Based on a study of a vulnerable region in Australia, we identify three processes through which the local community mobilized to disrupt local climate change adaptation. These included emphasizing uncertainty about the science of climate change, encouraging fear about property prices, and repositioning property owners as victims of climate adaptation policy. We argue that this response to climate adaptation constitutes the production of reflexive ignorance, which reinforces skepticism around scientific authority and defends particular economic interests.